EGCG Prevents High Fat Diet-Induced Changes in Gut Microbiota, Decreases of DNA Strand Breaks, and Changes in Expression and DNA Methylation of Dnmt1 and MLH1 in C57BL/6J Male Mice. (4th January 2017) - Remely, Marlene; Ferk, Franziska; Sterneder, Sonja; Setayesh, Tahereh; Roth, Sylvia; Kepcija, Tatjana; Noorizadeh, Rahil; Rebhan, Irene; Greunz, Martina; Beckmann, Johanna; Wagner, Karl-Heinz; Knasmüller, Siegfried; et al.
Abstract : Obesity as a multifactorial disorder involves low-grade inflammation, increased reactive oxygen species incidence, gut microbiota aberrations, and epigenetic consequences. Thus, prevention and therapies with epigenetic active antioxidants, (- )-Epigallocatechin-3-gallate (EGCG), are of increasing interest. DNA damage, DNA methylation and gene expression of DNA methyltransferase 1, interleukin 6, and MutL homologue 1 were analyzed in C57BL/6J male mice fed a high-fat diet (HFD) or a control diet (CD) with and without EGCG supplementation. Gut microbiota was analyzed with quantitative real-time polymerase chain reaction. An induction of DNA damage was observed, as a consequence of HFD-feeding, whereas EGCG supplementation decreased DNA damage. HFD-feeding induced a higher inflammatory status. Supplementation reversed these effects, resulting in tissue specific gene expression and methylation patterns of DNA methyltransferase 1 and MutL homologue 1 . HFD feeding caused a significant lower bacterial abundance. The Firmicutes/Bacteroidetes ratio is significantly lower in HFD + EGCG but higher in CD + EGCG compared to control groups. The results demonstrate the impact of EGCG on the one hand on gut microbiota which together with dietary components affects host health. On the other hand effects may derive from antioxidative activities as well as epigenetic modifications observed on CpG methylation but also likely to include other epigenetic elements.